Consumers’ response on local food franchise facebook advertising / Muhamad Kamarul Zaman Mohd Ariffin - Mohd Ariffin, Muhamad Kamarul Zaman (2018)
In this digital era, social media is one of the most important tool in marketing to any business as it is widely used by both potential customer and organization in engaging a positive relationship with each other. In Malaysia, the trend of using social media as a marketing medium are being practiced by the industry players in many sectors as it is way more convenient in connecting the organization with customers directly on their daily devices, cost friendly with high successful rate. In foodservice sector, the usage of social media marketing is also being widely practiced by not only small group of managers who know the benefits of the service but also involve beginners and entrepreneurs to advertise their products into the competing market. Local food franchise also adapting the strategy to position their brands and compete with other international brands. Social media such as Facebook, Twitter and Instagram are seem to be designed for this marketing purposes by serving their own business tools to the managers who want to use the service. The social media business tools give managers the ability to create their own page, and market their advertisement as sponsored ads which the social media platform will help the ads to reach their potential customer based on what preference the manager choose. Therefore, the purpose of this this study is to analytically find out the consumers’ response on the local food franchises Facebook advertisement and how it influences the consumers’ purchase intention.